Microbial metabolite-based ultra-low temperature biochemical stable refrigerant and preparation method thereof
Patent Information
- Application Number
- CN202610916329.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-20
AI Technical Summary
然而,现有的多相复合载冷剂在实际应用中仍存在以下问题:一是相间稳定性差,多相体系在长期储存或反复冻融过程中,分散相易发生团聚、沉降或相分离,导致组分迁移、功能层失效,载冷剂的性能衰减迅速;二是各相功能协同不足,抗冻组分、导热填料和冰晶抑制因子难以在空间上实现优化分布,例如提高甘油含量虽能降低冰点但会导致导热系数下降,增加纳米填料虽能提升导热却易诱发相分离;三是环境友好性欠佳,多数多相载冷剂仍依赖石油来源的防冻剂(如乙二醇)和合成聚合物,生物降解性差,对环境造成负担
1、由于本申请采用外相连续基体液、中间功能分散相和核心内相的三相复合分散液态体系,并分别优化各相组成,使得载冷剂兼具良好的管道润湿性、高效导热性、超低温冰晶抑制能力和流动稳定性,避免了均相载冷剂在超低温下功能耦合不佳的问题。
Abstract
Description
Technical Field
[0001] This application relates to the field of refrigerant technology, and more specifically, to an ultra-low temperature biochemically stable refrigerant based on microbial metabolites and its preparation method. Background Technology
[0002] Refrigerants are the mediums that transfer heat in indirect cooling systems and are widely used in food freezing, biopharmaceutical preservation, and low-temperature chemical reactions. However, in ultra-low temperature environments, such as -60°C, traditional refrigerants like water, brine, and ethylene glycol solutions suffer from problems such as ice crystal formation, a sudden increase in viscosity, and decreased heat transfer efficiency. In severe cases, this can lead to pipe freezing and cracking or system failure.
[0003] To improve overall performance at ultra-low temperatures, existing technologies have developed multiphase composite refrigerants. These refrigerants enrich components with different functions in different phase regions to achieve synergistic effects such as antifreeze, thermal conductivity, and lubrication. However, existing multiphase composite refrigerants still have the following problems in practical applications: First, poor interphase stability. During long-term storage or repeated freeze-thaw cycles, the dispersed phase is prone to aggregation, sedimentation, or phase separation, leading to component migration, functional layer failure, and rapid performance degradation of the refrigerant. Second, insufficient synergy among phases. Antifreeze components, thermally conductive fillers, and ice crystal inhibitors are difficult to optimize spatial distribution. For example, increasing glycerol content lowers the freezing point but reduces thermal conductivity, while adding nanofillers improves thermal conductivity but easily induces phase separation. Third, poor environmental friendliness. Most multiphase refrigerants still rely on petroleum-derived antifreeze (such as ethylene glycol) and synthetic polymers, which have poor biodegradability and impose a burden on the environment. Summary of the Invention
[0004] To improve the stability and environmental friendliness of refrigerants in ultra-low temperature environments, this application provides an ultra-low temperature biochemically stable refrigerant based on microbial metabolites and its preparation method.
[0005] In a first aspect, this application provides an ultra-low temperature biochemically stable refrigerant based on microbial metabolites, employing the following technical solution: A cryogenic biochemically stable coolant based on microbial metabolites, wherein the coolant is a three-phase composite dispersion liquid system, consisting of an external continuous matrix liquid, an intermediate functional dispersion phase, and a core internal phase, with a component transition zone formed between the three phases by an interfacial compatibilizer, the width of which is 10-25 μm; The external phase continuous matrix liquid comprises the following raw materials by mass percentage: 0.05-0.1% xanthan gum, 15-25% microbially fermented glycerol, and the balance being a methylcellulose / trehalose composite aqueous solution; The intermediate functional dispersed phase comprises the following raw materials in the following mass percentages: 2-3.5% KH570 modified flake boron nitride nanoparticles, 0.2-0.4% carbon nanotubes, 0.2-0.5% polyether modified organosilicon dispersant, 0.3-0.6% KH570 modified fumed silica, 0.5-1% propylene glycol, and the balance being a polyethylene glycol / polyvinyl alcohol blend aqueous solution; The core internal phase comprises the following raw materials by mass percentage: 2-4% linear polypropylene glycol, a mixed liquid phase of glycerol and water, 0.01-0.05% ice crystal recrystallization inhibitor protein, 0.01-0.05% trehalose, 0.05-0.1% Tween 80, and the balance being a linear polyvinyl alcohol sol dispersion medium, wherein the mass ratio of glycerol to water is ≥6:1; The interface compatibilizer is a mixture of polyethylene glycol-polypropylene glycol block copolymer and KH570, wherein the mass fraction of KH570 is 0.5-1.0%.
[0006] By adopting the above technical solution, the external continuous matrix fluid uses a methylcellulose / trehalose composite aqueous solution as the continuous phase matrix, compounded with microbially fermented glycerol and xanthan gum, to form a pseudoplastic fluid with high water content. This fluid can effectively wet the pipe wall, reduce flow resistance, and provide primary antifreeze protection. The intermediate functional dispersed phase uses a polyethylene glycol / polyvinyl alcohol blend aqueous solution as the dispersed phase matrix. By adding KH570-modified sheet-like boron nitride nanoparticles and carbon nanotubes, a highly efficient heat-conducting network is constructed, enhancing the heat transfer capacity of the refrigerant. The polyether-modified organosilicon dispersant ensures the uniform dispersion of the nanofiller in the dispersed phase. KH570-modified fumed silica further modulates the rheological properties of the intermediate functional dispersed phase. To prevent sedimentation and phase separation, propylene glycol acts as an auxiliary antifreeze agent, enhancing the fluidity of the intermediate functional dispersed phase at low temperatures. The core phase is a linear polyvinyl alcohol sol dispersion medium containing a high-concentration glycerol-water mixed liquid phase with a glycerol to water mass ratio ≥6:1. This high-proportion glycerol system effectively inhibits ice crystal nucleation. Furthermore, the core phase also contains a combination of ice crystal recrystallization inhibitor protein and trehalose. The ice crystal recrystallization inhibitor protein adsorbs onto the surface of tiny ice crystals, inhibiting their growth and recrystallization. Trehalose acts as a protein protectant and additional antifreeze factor; their synergistic effect significantly reduces freeze-thaw damage. Tween80, as a surfactant, helps the ice crystal recrystallization inhibitor protein to distribute uniformly in the glycerol-water phase. An interfacial compatibilizer forms a 10-25 μm wide component transition zone between the three phases, avoiding interphase stress concentration and phase separation, thus ensuring the stability of the entire liquid system during repeated freeze-thaw cycles.
[0007] Preferably, the mass ratio of the ice crystal recrystallization inhibitor protein to trehalose is 1:1.
[0008] By adopting the above technical solution and controlling the mass ratio of ice crystal recrystallization inhibitor protein to trehalose, the synergistic inhibitory effect of the two on ice crystal growth is significant. Trehalose can not only stabilize the protein structure, but also competitively adsorb onto the surface of ice crystals, further inhibiting ice crystal coarsening and extending the effective working time of the refrigerant at ultra-low temperatures.
[0009] Preferably, the purity of the microbially fermented glycerol is ≥99.5%.
[0010] By adopting the above technical solution, high-purity microbial fermented glycerol is derived from renewable resources, avoiding the influence of organic impurities (such as acrolein, chloroethanol, etc.) that may remain in chemically synthesized glycerol on the activity of ice crystal recrystallization inhibiting protein, while improving the biodegradability and environmental friendliness of the refrigerant.
[0011] Secondly, this application provides a method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites, using the following technical solution: A method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites includes the following steps: (1) Linear polyvinyl alcohol was prepared into a sol dispersion system, and microbial fermentation glycerol, ice crystal recrystallization inhibitor protein, trehalose and Tween80 were added. The mass ratio of glycerol to water was adjusted to ≥6:1. The mixture was stirred at low speed under nitrogen protection at 0-4℃ to obtain the core phase. (2) KH570 modified sheet-like boron nitride nanoparticles, carbon nanotubes, KH570 modified fumed silica are mixed with polyethylene glycol, polyvinyl alcohol, and propylene glycol aqueous solution. Polyether modified organosilicon dispersant is added. After ball milling, high-speed dispersion, and ultrasonic dispersion, the mixture is homogenized again at high speed to obtain an intermediate functional dispersed phase. (3) Dissolve methylcellulose, trehalose and xanthan gum in deionized water, swell and add microbial fermented glycerol to adjust the water content of the system, heat and mix well and then cool and keep the temperature constant to obtain an external continuous matrix liquid; (4) Prepare the interface compatibilizer in advance, add the interface compatibilizer to the core inner phase and stir to mix, then slowly add the intermediate functional dispersed phase and stir to form a composite intermediate system; after adding the interface compatibilizer again, slowly mix in the outer phase continuous matrix liquid and stir at low speed in a steady state to construct a three-phase composite liquid system with a micron-level transition zone. (5) The entire process is carried out in a dry nitrogen atmosphere, and the temperature is successively reduced to -5℃, -20℃ and -60℃ and kept warm for maturation. After maturation, the temperature is restored to room temperature. After the temperature is restored, the liquid ultra-low temperature refrigerant is obtained by bubbling with dry nitrogen and storing it in a sealed container.
[0012] By employing the above technical solutions, the core internal phase is homogenized by low-speed stirring under low-temperature nitrogen protection, avoiding the inhibition of protein activity loss due to ice crystal recrystallization. During the preparation of the intermediate functional dispersed phase, a multi-stage dispersion process—ball milling, high-speed dispersion, ultrasonication, and re-high-speed homogenization—ensures the uniform dispersion of boron nitride nanoparticles and carbon nanotubes in the polymer aqueous matrix, forming a stable thermally conductive filler network. In the three-phase composite construction, the stepwise addition of interfacial compatibilizers and control of the stirring rate promote the interpenetration of molecular chains between phases, forming a component transition zone with controllable width. The final segmented cooling and curing process simulates the cooling curve in actual use, gradually stabilizing the microstructure within each phase, avoiding phase separation and internal stress caused by rapid cooling, and improving the overall low-temperature stability of the coolant. After rewarming, dry nitrogen bubbling is used for stabilization, further removing any trace amounts of dissolved oxygen in the system and preventing protein oxidative inactivation.
[0013] Preferably, in step (1), the stirring and homogenization speed is 80-150 r / min, and the constant temperature stirring time is 30-60 min.
[0014] By adopting the above technical solution, the core internal phase is homogenized by low-speed stirring under low-temperature nitrogen protection, with the stirring speed controlled at 80-150 r / min and the time controlled at 30-60 min. This can not only ensure that the ice crystal recrystallization inhibitor protein, trehalose, Tween 80 and glycerol-water mixed liquid phase are fully and evenly dispersed, but also avoid protein denaturation and inactivation caused by the heat and mechanical stress generated by high-speed shearing. If the stirring time is too short, it will easily lead to uneven protein dispersion, while if the time is too long, it will increase energy consumption and may introduce air bubbles. The preferred range of this application takes into account both protein activity and process efficiency while ensuring the dispersion effect.
[0015] Preferably, in step (2), the ultrasonic dispersion is carried out in an ice bath at a temperature of 20-25°C, and the ball mill pre-dispersion speed is 300-500 r / min.
[0016] By adopting the above technical solution, a multi-stage dispersion process of ball milling-high-speed dispersion-ultrasound-re-high-speed homogenization is used in the preparation of the intermediate functional dispersed phase. The ball milling pre-dispersion speed is controlled at 300-500 r / min, which can initially open up the nano-boron nitride and carbon nanotube aggregates without destroying their plate-like and tubular structures; the ultrasonic dispersion is carried out in an ice bath at a temperature of 20-25℃ throughout, which not only utilizes the ultrasonic cavitation effect to achieve nanoscale dispersion of nanofillers in polymer aqueous solution, but also avoids the impact of local high temperature generated during the ultrasonic process on the stability of polyethylene glycol / polyvinyl alcohol blend aqueous solution system.
[0017] Preferably, in step (4), the width of the three-phase interface transition zone is stabilized at 10-25 μm by adjusting the stirring rate.
[0018] By adopting the above technical solution, the stirring rate is the key process parameter for controlling the width of the transition zone at the three-phase interface. When the stirring rate is fast, the interphase shearing effect is enhanced, the degree of interpenetration of molecular chains is reduced, the transition zone width is narrower, resulting in insufficient interphase bonding and easy phase separation during freeze-thaw processes. When the stirring rate is slow, the interphase diffusion is excessive, the transition zone width is wider, the functional differentiation of each phase decreases, and the synergistic effect of functions such as antifreeze, thermal conductivity, and ice crystal inhibition is weakened.
[0019] Preferably, in step (5), after the temperature is restored to room temperature, dry nitrogen is used for bubbling stabilization, and the bubbling stabilization time is 5-10 minutes.
[0020] By adopting the above technical solution, after the staged cooling and maturation process is completed and the system is brought back to room temperature, trace amounts of oxygen may be dissolved in the three-phase composite liquid system. During subsequent storage, this oxygen may slowly oxidize ice crystals, causing recrystallization and inhibiting protein activity. Stabilizing the system with dry nitrogen bubbling for 5-10 minutes utilizes the inert protective properties of nitrogen. Through the purging and displacement effects of the bubbles, dissolved oxygen is effectively removed from the system. Simultaneously, the bubbling process does not introduce additional mechanical shearing, avoiding protein damage. If the bubbling time is too short, oxygen removal will be incomplete; if the bubbling time is too long, too many bubbles may be introduced, affecting the homogeneity of the refrigerant.
[0021] In summary, this application has the following beneficial effects: 1. Because this application adopts a three-phase composite dispersion liquid system consisting of an external continuous matrix liquid, an intermediate functional dispersed phase, and a core internal phase, and optimizes the composition of each phase, the refrigerant has good pipeline wettability, high thermal conductivity, low temperature ice crystal suppression capability, and flow stability, thus avoiding the problem of poor functional coupling of homogeneous refrigerants at low temperatures.
[0022] 2. In this application, ice crystal recrystallization inhibitor protein and trehalose are preferably combined in a 1:1 mass ratio and distributed in a high-concentration glycerol-water phase in the core phase. The two work synergistically to effectively inhibit the nucleation and growth of ice crystals, reduce the risk of freezing of the refrigerant below -60°C, and extend its service life.
[0023] 3. This application uses high-purity glycerol derived from microbial fermentation to replace chemically synthesized glycerol, and combines it with biodegradable matrix materials such as methylcellulose and polyvinyl alcohol, thereby improving the environmental friendliness and biosafety of the refrigerant. Detailed Implementation
[0024] The present application will be further described in detail below with reference to the embodiments. Preparation example of KH570 modified sheet-like boron nitride nanoparticles
[0025] Preparation Example 1 10 g of flake-shaped boron nitride nanoparticles were added to 200 mL of a 9:1 (v / v) ethanol / water mixture and ultrasonically dispersed for 30 min. The pH was adjusted to 4.0 with glacial acetic acid, and then 2 g of KH570 was added. The mixture was mechanically stirred in a 60 °C water bath for 6 h. After the reaction was complete, the mixture was centrifuged, washed three times with anhydrous ethanol, vacuum dried at 60 °C for 24 h, and then ground through a 200-mesh sieve to obtain KH570-modified flake-shaped boron nitride nanoparticles. Preparation example of KH570 modified fumed silica
[0026] Preparation Example 2 10 g of fumed silica was dispersed in 200 mL of toluene, and 1.5 g of KH570 was added. The mixture was refluxed at 110 °C for 8 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with toluene, and dried under vacuum at 60 °C for 12 h to obtain KH570 modified fumed silica. Example of preparing a protein solution inhibiting ice crystal recrystallization
[0027] Preparation Example 3 The recombinant ice crystal recrystallization inhibitor protein derived from Chlamydomonas antarctica, which was expressed and purified, was dissolved in 10 mM phosphate buffer (pH 7.0) to prepare a 1 mg / mL stock solution. After filtration and sterilization, the solution was stored at 4°C for later use. Example Example 1
[0028] A method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites includes the following steps: (1) Preparation of the core inner phase: Linear polyvinyl alcohol with a degree of alcoholysis of 88% and a molecular weight of about 30,000 was added to deionized water, heated to 90°C to dissolve and then cooled to obtain a sol dispersion system with a mass fraction of 5%; 82.3g of the sol dispersion system was taken, and 15g of microbial fermented glycerol with a purity of 99.7%, 0.03g of the ice crystal recrystallization inhibitor protein solution prepared in Example 3, 0.03g of trehalose, and 0.05g of Tween 80 were added. Deionized water was added to make the mass ratio of glycerol to water reach 6:1; the mixture was stirred and homogenized at 120r / min for 45min under nitrogen protection at 2°C to obtain the core inner phase.
[0029] (2) Preparation of intermediate functional dispersed phase: Take 8g of polyethylene glycol PEG400, 2g of polyvinyl alcohol, and 0.5g of propylene glycol, dissolve them in 84.6g of deionized water, and stir until completely dissolved; add 2.8g of KH570 modified sheet-like boron nitride nanoparticles prepared in Preparation Example 1, 0.3g of carbon nanotubes, 0.4g of polyether modified organosilicon dispersant, and 0.4g of KH570 modified fumed silica prepared in Preparation Example 2 in sequence; first, pre-disperse in a ball mill at 400r / min for 1h, then disperse in a high-speed disperser at 3000r / min for 20min, then disperse in an ice bath at 23℃ using ultrasonic dispersion, and finally disperse again at 5000r / min for 15min to obtain intermediate functional dispersed phase.
[0030] (3) Preparation of continuous external phase matrix solution: 0.08 g methylcellulose, 0.02 g trehalose and 0.08 g xanthan gum were dissolved in 73.82 g deionized water and swollen for 2 h. Then 26 g microbial fermented glycerol was added, heated to 60 °C and mixed, and cooled to 25 °C to obtain continuous external phase matrix solution.
[0031] (4) Construction of the three-phase composite system: Prepare an interfacial compatibilizer by mixing polyethylene glycol-polypropylene glycol block copolymer F127 with KH570, where the mass fraction of KH570 is 0.8%; take 100g of the core inner phase, add 0.5g of the interfacial compatibilizer, and stir at 200r / min for 15min. Then slowly incorporate 35g of the intermediate functional dispersed phase and stir at 300r / min for 30min to form a composite intermediate system; add another 0.3g of the interfacial compatibilizer, and then slowly mix in 65g of the outer phase continuous matrix liquid, and stir at a low speed of 150r / min for 40min. The width of the three-phase interface transition zone is stabilized at 15-20μm by adjusting the stirring rate.
[0032] (5) Curing and post-treatment: The entire process was carried out in a dry nitrogen atmosphere, and the temperature was successively reduced to -5℃ and held for 1 hour, -20℃ and held for 2 hours, and -60℃ and held for 3 hours for curing. After curing, the temperature was naturally restored to room temperature. After restoration, the temperature was stabilized by bubbling with dry nitrogen for 8 minutes, and then sealed and stored to obtain a liquid ultra-low temperature refrigerant. Example 2
[0033] The difference between Example 2 and Example 1 is that in Example 2, in step (1), the purity of microbial fermented glycerol is 99.9%, and the amount of protein and trehalose added is 0.05g; in step (4), the stirring rate when the external phase is mixed in is 120r / min, so that the width of the three-phase interface transition zone is stabilized at 20-25μm. Example 3
[0034] The difference between Example 3 and Example 1 is that in Example 3, in step (1), the stirring and homogenization speed is 200 r / min and the constant temperature stirring time is 20 min. Example 4
[0035] The difference between Example 4 and Example 1 is that in Example 4, in step (2), the ultrasonic dispersion was carried out without ice bath temperature control, and the ball mill pre-dispersion speed was 600 r / min. Example 5
[0036] The difference between Example 5 and Example 1 is that in Example 5, in step (4), the width of the three-phase interface transition zone is stabilized at 5-8 μm by increasing the stirring rate. Example 6
[0037] The difference between Example 6 and Example 1 is that in Example 6, in step (5), the stabilization time using dry nitrogen bubbling after rewarming is 3 minutes. Comparative Example
[0038] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, ice crystal recrystallization inhibitor protein and trehalose are not added to the core inner phase in step (1), but are replaced with an equal amount of deionized water.
[0039] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, in step (1), the mass ratio of glycerol to water is adjusted to 3:1; the specific steps are as follows: take 82.3g of linear polyvinyl alcohol sol dispersion system, add 8g of microbial fermented glycerol, 0.03g of ice crystal recrystallization inhibitor protein, 0.03g of trehalose, 0.05g of Tween80, and add deionized water to make the mass ratio of glycerol to water 3:1.
[0040] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, KH570-modified sheet-like boron nitride nanoparticles and carbon nanotubes are not added to the intermediate functional dispersed phase in step (2), but are replaced by an equal amount of polyethylene glycol / polyvinyl alcohol blended aqueous solution.
[0041] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, all components are directly mixed without constructing a three-phase composite dispersion system. The specific steps are as follows: all raw materials of the core inner phase, intermediate functional dispersion phase and outer continuous matrix liquid in Example 1 are mixed at one time, and homogenized by high-speed stirring at 500r / min for 60min. The transition zone is not constructed in steps, and the temperature is directly cooled to -60℃ in one step without staged cooling and maturation. Performance testing
[0042] The refrigerant was prepared according to the methods of Examples 1-6 and Comparative Examples 1-4, and its low-temperature stability, ice crystal inhibition ability, thermal conductivity, viscosity, and freeze-thaw cycle stability were tested. The results are recorded in Table 1.
[0043] Low temperature stability test: Store the refrigerant sample in a constant temperature environment of -60℃ for 30 days and observe whether there is phase separation, precipitation or gelation; Evaluation criteria: No obvious phase separation and precipitation is "excellent", trace layering but can be restored after shaking is "good", irreversible phase separation or precipitation is "poor".
[0044] Ice crystal suppression ability test: Differential scanning calorimetry (DSC) was used to cool the sample to -80℃ at a rate of 10℃ / min and then heat it up at a rate of 5℃ / min, and the freezing point was recorded. At the same time, the size and morphology of ice crystals in the sample were observed at -60℃ using a cryo-microscope, and the average ice crystal particle size was measured.
[0045] Thermal conductivity test: The thermal conductivity of the refrigerant was tested at -60℃ using a transient hot-wire thermal conductivity meter.
[0046] Viscosity test: The apparent viscosity of the samples was tested at -40°C and 25°C using a rotational viscometer to evaluate low-temperature flowability.
[0047] Freeze-thaw cycle stability test: The sample was frozen at -60℃ for 24 hours and then thawed at room temperature for 24 hours, and the cycle was repeated 10 times; the viscosity change rate before and after the cycle was tested.
[0048] Table 1. Test results of the refrigerant Example 1 excellent -82.3 2.1 0.68 1280 6.2 Example 2 excellent -83.1 1.9 0.65 1350 5.8 Example 3 good -81.5 3.8 0.66 1320 12.4 Example 4 good -80.9 4.2 0.51 1580 15.7 Example 5 Poor and slightly stratified -81.7 3.1 0.62 1410 21.3 Example 6 excellent -82.0 2.5 0.67 1290 8.1 Comparative Example 1 good -58.4 45.6 0.60 1520 35.6 Comparative Example 2 Poor and severely stratified -42.7 62.3 0.55 1850 48.2 Comparative Example 3 excellent -81.9 2.3 0.31 1250 7.5 Comparative Example 4 Poor and completely stratified -76.5 15.8 0.48 2100 62.5 Example 1 excellent -82.3 2.1 0.68 1280 6.2 As shown in Table 1, Examples 1-2, and Comparative Example 1, the cryogenic biochemically stable refrigerant prepared in Examples 1-2 possesses an extremely low freezing point, a small average ice crystal size, a high thermal conductivity at -60℃, and excellent freeze-thaw cycle stability. In Examples 1-2, in a three-phase composite dispersion liquid system, ice crystal recrystallization inhibitor protein and trehalose were compounded at a near 1:1 mass ratio and concentrated in a high-concentration glycerol-water phase within the core phase. The two components synergistically adsorbed onto the surface of the small ice crystals, effectively inhibiting ice crystal nucleation, growth, and recrystallization, thereby significantly reducing the freezing point and controlling the ice crystal size. Simultaneously, the KH570-modified sheet-like boron nitride nanoparticles and carbon nanotubes in the intermediate functional dispersion phase constructed a highly efficient thermally conductive network, avoiding the increase in thermal resistance caused by filler agglomeration in the outer or inner phase, thus maintaining a high thermal conductivity at cryogenic temperatures.
[0049] In Comparative Example 1, without the addition of ice crystal recrystallization inhibitor protein and trehalose, the freezing point significantly increased to -58.4℃, and the average ice crystal size increased sharply to 45.6μm. This indicates that without the protein-trehalose synergistic inhibition system, the refrigerant cannot effectively control ice crystal growth at ultra-low temperatures, resulting in severe ice crystal coarsening. In Comparative Example 2, the mass ratio of glycerol to water was reduced to 3:1, and the ice crystal inhibition ability of the core phase decreased significantly, with a freezing point of only -42.7℃. Severe stratification also occurred, indicating that a high proportion of glycerol is a necessary condition for maintaining the ultra-low temperature antifreeze performance of the core phase. When the proportion is insufficient, not only will ice crystal inhibition fail, but the stability of the three-phase system will also be compromised.
[0050] As can be seen from Examples 1 and 3, the thermal conductivity of the intermediate functional dispersed phase of Comparative Example 3 without the addition of KH570-modified sheet-like boron nitride nanoparticles and carbon nanotubes decreased significantly from 0.68 W / (m·K) to 0.31 W / (m·K) at -60℃. This indicates that the nano-thermal conductive filler in the intermediate functional dispersed phase is beneficial for maintaining the high-efficiency heat transfer capability of the refrigerant at ultra-low temperatures. Without the filler, the thermal conductivity of the refrigerant mainly depends on the continuous liquid phase. However, the molecular motion of the liquid phase is restricted at -60℃, and the thermal conductivity naturally decreases significantly. At the same time, other properties of Comparative Example 3 did not show significant deterioration, indicating that the three-phase partitioning design effectively achieved functional decoupling—the thermal conductivity function is concentrated in the intermediate phase, and the antifreeze function is concentrated in the inner phase.
[0051] As can be seen from Example 1 and Comparative Example 4, Comparative Example 4 directly mixed all components without constructing a three-phase composite dispersion system or performing staged cooling and ripening. The result was complete stratification, with a viscosity change rate as high as 62.5% after 10 freeze-thaw cycles, a freezing point increase to -76.5℃, and an average ice crystal size increase to 15.8 μm. This indicates that direct mixing prevents components of different polarities from spontaneously forming stable phase distributions. The lack of a gradient transition between the high-concentration glycerol aqueous solution, polymer matrix, and nanofiller leads to rapid macroscopic phase separation during storage and freeze-thaw cycles. Simultaneously, the absence of a staged cooling and ripening step prevents the gradual stabilization of the internal microstructures of each phase, and the internal stress generated by rapid cooling further exacerbates phase separation.
[0052] As can be seen from Examples 3 and 1, Example 3 increased the stirring speed and shortened the stirring time during the preparation of the core phase, resulting in a decrease in low-temperature stability from "excellent" to "good," an increase in the average ice crystal particle size from 2.1 μm to 3.8 μm, and an increase in the viscosity change rate after 10 freeze-thaw cycles from 6.2% to 12.4%. This is because excessively high stirring speed and excessively short stirring time are not conducive to the gentle and sufficient dispersion of the ice crystal recrystallization inhibitor protein in the glycerol-aqueous phase. Some proteins are inactivated due to mechanical shear force, and the dispersion uniformity decreases, leading to a weakening of the ice crystal inhibition ability and a reduction in the long-term stability of the system.
[0053] As can be seen from Examples 4 and 1, in Example 4, during the preparation of the intermediate functional dispersed phase, the ultrasonic dispersion was not temperature-controlled using an ice bath, and the ball milling pre-dispersion speed was increased to 600 r / min. The thermal conductivity at -60℃ decreased, the viscosity at -40℃ increased, and the viscosity change rate after 10 freeze-thaw cycles increased to 15.7%. This indicates that the lack of temperature control during ultrasonication easily leads to localized overheating, causing degradation or cross-linking of the polymer chains in the polyethylene glycol / polyvinyl alcohol blend aqueous solution system, thus disrupting the stability of the dispersed phase. Excessively high ball milling speeds may damage the sheet-like structure of boron nitride nanoparticles and the aspect ratio of carbon nanotubes, reducing the anisotropic heat transfer efficiency of the thermally conductive filler. Simultaneously, excessive fine powder production exacerbates re-agglomeration, resulting in insufficient thermal network construction and abnormally high viscosity at low temperatures.
[0054] As can be seen from Examples 5 and 1, Example 5, by increasing the stirring rate to narrow the three-phase interface transition zone width to 5-8 μm, exhibited poor low-temperature stability and slight stratification, with a viscosity change rate as high as 21.3% after 10 freeze-thaw cycles. This indicates that the transition zone width is a key structural parameter of this application. An excessively narrow transition zone means insufficient interphase molecular chain penetration, the interface compatibilizer failing to fully exert its gradient bridging effect, and weak bonding between the three phases. This makes microphase separation prone to occur during ultra-low temperature storage and freeze-thaw cycles, leading to component migration and drastic viscosity changes. Controlling the transition zone width within the range of 10-25 μm ensures sufficient interphase bonding strength, thereby guaranteeing long-term stability.
[0055] As can be seen from Examples 6 and 1, in Example 6, the stabilization time of dried nitrogen bubbling after rewarming was shortened to 3 minutes, and the viscosity change rate after 10 freeze-thaw cycles increased from 6.2% to 8.1%. A bubbling time that is too short cannot adequately remove the trace amounts of dissolved oxygen in the system. The residual oxygen may slowly oxidize the ice crystal recrystallization inhibitory protein in the core phase during subsequent storage and freeze-thaw cycles, leading to the loss of its active components and thus weakening the ice crystal inhibition ability and system stability. A bubbling time controlled at 5-10 minutes effectively removes oxygen without introducing excessive bubbles, balancing protein protection and refrigerant homogeneity.
[0056] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A cryogenic biochemically stable refrigerant based on microbial metabolites, characterized in that, The coolant is a three-phase composite dispersion liquid system, consisting of an external continuous matrix liquid, an intermediate functional dispersion phase, and a core internal phase. The three phases are connected by an interfacial compatibilizer to form a component transition zone with a width of 10-25 μm. The external phase continuous matrix liquid comprises the following raw materials by mass percentage: 0.05-0.1% xanthan gum, 15-25% microbially fermented glycerol, and the balance being a methylcellulose / trehalose composite aqueous solution; The intermediate functional dispersed phase comprises the following raw materials in the following mass percentages: 2-3.5% KH570 modified flake boron nitride nanoparticles, 0.2-0.4% carbon nanotubes, 0.2-0.5% polyether modified organosilicon dispersant, 0.3-0.6% KH570 modified fumed silica, 0.5-1% propylene glycol, and the balance being a polyethylene glycol / polyvinyl alcohol blend aqueous solution; The core internal phase comprises the following raw materials by mass percentage: 2-4% linear polypropylene glycol, a mixed liquid phase of glycerol and water, 0.01-0.05% ice crystal recrystallization inhibitor protein, 0.01-0.05% trehalose, 0.05-0.1% Tween 80, and the balance being a linear polyvinyl alcohol sol dispersion medium, wherein the mass ratio of glycerol to water is ≥6:1; The interface compatibilizer is a mixture of polyethylene glycol-polypropylene glycol block copolymer and KH570, wherein the mass fraction of KH570 is 0.5-1.0%.
2. The cryogenic biochemically stable refrigerant based on microbial metabolites according to claim 1, characterized in that, The mass ratio of the ice crystal recrystallization inhibitor protein to trehalose is 1:
1.
3. The cryogenic biochemically stable refrigerant based on microbial metabolites according to claim 1, characterized in that, The purity of the microbially fermented glycerol is ≥99.5%.
4. A method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Linear polyvinyl alcohol was prepared into a sol dispersion system, and microbial fermentation glycerol, ice crystal recrystallization inhibitor protein, trehalose and Tween80 were added. The mass ratio of glycerol to water was adjusted to ≥6:
1. The mixture was stirred at low speed under nitrogen protection at 0-4℃ to obtain the core phase. (2) KH570 modified sheet-like boron nitride nanoparticles, carbon nanotubes, KH570 modified fumed silica are mixed with polyethylene glycol, polyvinyl alcohol, and propylene glycol aqueous solution. Polyether modified organosilicon dispersant is added. After ball milling, high-speed dispersion, and ultrasonic dispersion, the mixture is homogenized again at high speed to obtain an intermediate functional dispersed phase. (3) Dissolve methylcellulose, trehalose and xanthan gum in deionized water, swell and add microbial fermented glycerol to adjust the water content of the system, heat and mix well and then cool and keep the temperature constant to obtain an external continuous matrix liquid; (4) Prepare the interface compatibilizer in advance, add the interface compatibilizer to the core inner phase and stir to mix, then slowly add the intermediate functional dispersed phase and stir to form a composite intermediate system; after adding the interface compatibilizer again, slowly mix in the outer phase continuous matrix liquid and stir at low speed in a steady state to construct a three-phase composite liquid system with a micron-level transition zone. (5) The entire process is carried out in a dry nitrogen atmosphere, and the temperature is successively reduced to -5℃, -20℃ and -60℃ and kept warm for maturation. After maturation, the temperature is restored to room temperature. After the temperature is restored, the liquid ultra-low temperature refrigerant is obtained by bubbling with dry nitrogen and storing it in a sealed container.
5. The method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites according to claim 4, characterized in that, In step (1), the stirring and homogenization speed is 80-150 r / min, and the constant temperature stirring time is 30-60 min.
6. The method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites according to claim 4, characterized in that, In step (2), the ultrasonic dispersion is carried out in an ice bath at a temperature of 20-25℃, and the ball mill pre-dispersion speed is 300-500r / min.
7. The method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites according to claim 4, characterized in that, In step (4), the width of the three-phase interface transition zone is stabilized at 10-25 μm by adjusting the stirring rate.
8. The method for preparing an ultra-low temperature biochemically stable refrigerant based on microbial metabolites according to claim 4, characterized in that, In step (5), after the temperature is restored to room temperature, dry nitrogen is used for bubbling stabilization, and the bubbling stabilization time is 5-10 minutes.